POTENSI BIOMASSA DAN KARBON AKAR TEGAKAN PINUS (Pinus merkusii Jung et de Vriese) DI HUTAN RAKYAT DESA HINALANG, KABUPATEN SIMALUNGUN, PROVINSI SUMATERA UTARA - , IVAN H. PURBA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Forest is one alternative that can be used to reduce the content of carbon dioxide (CO2) in the atmosphere. Forests have a major influence on the absorption of CO2 in the atmosphere. Therefore it is necessary to do research on CO2 storage by the forest to find out information about the absorb of carbon dioxide (CO2). Including the one of found on pine stands in community forest.Biomass and carbon content measurement was done in below ground, which is the root. The research was performed at community forest in Hinalang village, Simalungun dictrict, North Sumatera.Sample pine root biomass and carbon using longging stubs with diameter variations. The research method is divided into three stage,namely stage I: Measurement of biomass and carbon content of the root organ, stage II: Preparation of allometric equations, and stage III: Assessment of the potential of biomass and carbon content of the roots and the amount of CO2 that can be absorbed by the roots of pine stands in hinalang village community forest. The average result of biomass content with 26,2 cm of diameters is as follow : stem root is 7,169 kg ( 44,611 %), medium root is 8,023 kg (49,925%),root fiber is 0,878 kg (5,464 %). While the carbon content in one tree is as follow: stem root is 3,613 kg (44,634 %), medium root is 4,09 kg (50,221